Articulations of Local Governance in Timor-Leste : Lessons for Local Development under Decentralization - Butterworth, David; Dale, Pamela (World Bank, Washington, DC, 2018)
In pursuing a decentralization policy that sets out to devolve elements of state authority to municipalities, the Government of Timor-Leste faces a key challenge: how to combine different types of governance systems that have legitimacy at local and state levels. In order to inform this process, this policy note looks at how communities and local government currently work together to plan and implement local development initiatives. It attempts to answer the question, 'what steps might the government of Timor-Leste take to amplify the voice of citizens in development planning, and the responsiveness of the state to those voices?' This note informs current discussions on community-planning processes, dispute-resolution and complaints mechanisms within local development programs, and other important aspects of the decentralization agenda through a perspective informed by in-depth, local-level policy analysis.